Which Country is Truly Developed? COVID-19 has Answered the Question - Jeffrey S. Freed; Soo Y. Kwon; Hannah Jacobs El; Michael Gottlieb; Ram Roth (Ubiquity Press, 2020)
The developed countries of the world were ill-prepared for the pandemic that they have suffered. When we compare developed to developing countries, the sophisticated parameters we use do not necessarily address the weaknesses in the healthcare systems of developed countries that make them susceptible to crises like the present pandemic. We strongly suggest that better preparation for such events is necessary for a country to be considered developed.